Ernst Mach Dan Ekonomi Pikiran - Karlina Supelli (STF Driyarkara - Diskursus, 2012)
Abstract: Ernst Mach stands as a representative figure of the positivist philosophy of science at the turn of the twentieth century, yet he is by far the most misunderstood scientist-philosopher. The misunderstanding is largely caused by his epistemological rejection of the use of hypothetical entities that are ordinarily posited by scientists. He also argued against the mechanistic worldview which dominated scientific investigations in the nineteenth century. This essay will demonstrate that Mach’s positivism differs from the earlier positivism of August Comte. His anti metaphysical stance is deeply-rooted in his physical phenomenology, guided by the economy of thought in pursuit of the unity of science. In Mach’s view, scientific theories are merely biological tools for organizing experience by means of the fewest possible concepts, and all metaphysical elements are to be eliminated from science as methodologically and epistemologically superfluous. But Mach’s thesis of the unification of science does not share the common concern of the logical positivists to reduce various scientific statements to physical language. While Mach’s philosophy of science clearly exhibits a miscalculation of the strength of scientific conceptual tools, his physical phenomenology serves as a bridge between theory and experiment which has proved to be fruitful. Keywords: The economy of thought, evolution, element, physical phenomenology, the unity of science, instrumentalism, emphirical realism. Abstrak: Ernst Mach tampil sebagai tokoh representatif dari Filsafat Ilmu Pengetahuan positivis pada peralihan menuju abad ke-20, sekaligus sebagai ilmuwan-filsuf yang paling disalahpahami. Kesalahpahaman tersebut sebagian besar disebabkan oleh penolakan epitemologisnya terhadap penggunaan wujud-wujud hipotetis yang kerap diajukan oleh para ilmuwan. Ia juga melawan cara pandang mekanistis yang mendominasi penyelidikan ilmiah pada abad ke-19. Artikel ini memperlihatkan bahwa positivisme Mach berbeda dengan positivisme August Comte yang mendahuluinya. Pandangan anti-metafisis Mach berakar sangat dalam pada fisika fenomenologi yang dipandu oleh ekonomi pikiran untuk mencapai sains terpadu. Dalam pandangan Mach, teori-teori ilmiah semata-mata sarana biologis untuk menata pengalaman dengan memanfaatkan sesedikit mungkin konsep, dan semua elemen metafisika perlu disingkirkan dari sains karena secara metodologis dan epistemologis tidak bermanfaat. Namun, tesis Mach tentang sains terpadu tidak sejalan dengan gagasan para positivis logis yang mereduksi berbagai macam pernyataan ilmiah ke dalam bahasa fisika. Sementara Filsafat Ilmu Pengetahuan Mach jelas-jelas keliru dalam memperhitungkan kekuatan piranti-piranti konseptual sains, fisika fenomenologi yang menjembatani teori dan eksperimen telah terbukti sangat bermanfaat. Kata-kata kunci: Ekonomi pikiran, evolusi, elemen, fisika fenomenologi, sains terpadu, instrumentalisme, realisme empiris.